HUBUNGAN PENDIDIKAN DAN PELATIHAN TERHADAP KINERJA ANGGOTA SECURITY PT. G4S SECURITY SERVICES DI PROYEK BLOK CEPU - Budi Santoso (Jurnal Manajemen dan Penelitian Akuntansi (JUMPA), 2012)
This study examines the relationship of education and training on the performance of members of the security PT. G4S Security Services at Cepu block project. Using descriptive research, aims to make a systematic exposure or description, actual and accurate information on the facts, as well as the properties of the investigated phenomena relations. The population in this study were members of security PT. G4S Security Services. While this dipenelitian samples taken from about 61% of the total number of members of the security PT. G4S. Data collection method used is the method of sampling. While data collection techniques in a way: Observation, interviews and questionnaires / questionnaire. Methods of data analysis is descriptive quantitative study that leads to, the use of statistics by the formula "correlation." In conducting this research, the approach of survey, interviews and by giving questionnaires to the respondents. From the research result that performance is not only influenced by formal education. It is evident from the results of interviews and questionnaires were conducted in the field showed that education and training is much greater influence.